System dynamics modelling for e-government implementation: a case study in Bandung City, Indonesia - Alfanura, Farah; Arai, Takeshi; Putro, Utomo Sarjono (Jurnal Manajemen Teknologi, 2010)
Governments  around  the  world  have  developed  e-Government  programs  hoping  to  obtain  great benefits. However, many e-Government projects have failed to deliver their promises. Some of such failures  are  thought  to  be  the  results  of  lack  of  understanding  about  the  relationships  among 'technologies',  'information  use',  'organizational  factors',  'social  contexts  involved  in  the  selection, implementation and use of information and communication technologies (ICT)'. These factors stated above might have produced mismatches and unintended consequences. This research draws on not a few precedent studies as to those factors, and the case of the e-Government program in Bandung municipality, Indonesia, is assumed as a typical example of municipalities in developing nations. In this study, a simulation tool which helps to find the best way to create the efficient and useful e-Government is presented. In particular, the model, which is the core of the simulation tool, takes not only the supply side perspective which describes the mechanism of creating and operating the e-Government system but also the demand side perspective which explains the people's intention of communicating with the eGovernment  and  their  behaviors  toward  it.  The  simulation  tool  is  constructed  based  on System Dynamics as an integrated and comprehensive approach to understand the e-Government and its use. Because of lack of suitable statistical data, simulations were carried out by using subjectively estimated but plausible values of parameters after the sensitivity analysis. From the results of simulations, very complicated trade-off relationships among the allocated project budgets to different types of programs were suggested.Keywords: e-government, demand side perspective, supply side perspective, system dynamics